PEMETAAN STATUS UNSUR HARA C-ORGANIK DAN NITROGEN DI PERKEBUN NANAS (Ananas comosus L. Merr) RAKYAT DESA PANRIBUAN KECAMATAN DOLOK SILAU KABUPATEN - Rosmenda Ginting Rosmenda Ginting; Razali Razali; Zulkifli Nasution (Jurnal Agroekoteknologi, 2013)
ROSMENDA GINTING:Mapping of Nitrogen and C-Orgnic status on Pineapple(Ananas comosus L. Merr) plantations owned by people at the village of Panribuan Subdistrict ofDolok Silau Simalungun District superinted by Ir. Razali, MP. And Prof.Ir. Zulkifli Nasution,M. Sc.,Ph.D. This research purpose to make a mapping of Nitrogen and C-Orgnic status onPineapple plantations owned by people at the village of Panribuan Subdistrict of Dolok SilauSimalungun District The research start to do on October 2012 until January 2013. Method of takingsample uses the free method grid survey with detail scale and use correlation method to analysisdata, with interpretating in mapping Nitrogen and C-Organic. Parameter that analysis in laboratoryis Nitrogen and C-Orgnic status. The result of research showing that status Nitrogen devided by 1status such as; medium (35,44 ha), C-Organic devided by 4 status such as ; Low (0,19 ha), Medium(1,01 ha), high (12,89 ha), and highest (21,35 ha).C/N devided by 3 status such as ; Low (1,95 ha),Medium (11,70 ha) and high (21,79 ha). From the analysis data using correlation method, knownthat the no effect on the production are Nitrogen and C-Organic but that effect are C/N.Key words: Mapping, Nitrogen, C-Organic and C/N